Introducing Dayak Culture for Elementary School Students through Huma Betang Philosophical Poems - Diplan Diplan; Misnawati Misnawati; Wahidin Wahidin; Widya Permata Dilla; Wahyu Nugroho; Siti Patimah; Alimuddin A Djawat; Aam Rifaldi Khunaifi; Ade Salahudin Permadi; Anwarsani Anwarsani; Nabila Salwa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Dayak culture offers a wealth of noble values that can positively shape the character of elementary school students. This paper aims to: (1) identify the values of Dayak culture contained in the poem